The Effect of Murottal Al-Qur'an on the Anxiety of Pregnant Women in the Third Trimester in the Independent Practice of Midwives in the Bandung City Region - Fikriya; Widiawati, Ida; Fatimah, Yulia Ulfah (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Background: Anxiety is still widespread among pregnant women in Indonesia, and the frequency of this condition is relatively significant. During the third trimester of pregnancy, pregnant women experience a higher level of anxiety compared to the previous trimester. This is because they are more concerned about the labor and delivery procedure that they will go through as well as the pain that they will face during the birth process—taking in the murottal of the Al-Qur'an, which has the potential to induce a soothing effect.    Purpose: The aim of this study is to investigate how murottal Al-Qur'an influences third trimester pregnant women's anxiety level. Methode: The study design was a quasi-experiment with a control design that was used before and after the experiment. The study sample was made up of 60 pregnant women from Bandung who were in their third trimester and were between 28 and 36 weeks along. There were 30 expecting women in each of the two groups: the control group and the intervention group. Anxiety observation sheets were used to gather information. The results were looked at with the Mann Whitney test. Result: The intervention group was found to have a mean difference of 9.27, while the control group had a mean difference of 1.17. The Mann-Whitney test results, which were obtained by comparing the posttest results of the intervention group and the control group, indicated that murottal Al-Qur'an had a significant impact on the reduction of anxiety in third-trimester expectant women (p value = 0.017 < 0.05). Conclusion: Murottal al-Qur'an affects anxiety of third-trimester pregnant women.. Suggestion: It is hoped that future researchers will carry out further research by adding variables that can influence the anxiety of pregnant women in the third trimester and a larger number of respondents studied.